2017
DOI: 10.1242/dev.142554
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide identification of regulatory elements in Sertoli cells

Abstract: A current goal of molecular biology is to identify transcriptional networks that regulate cell differentiation. However, identifying functional gene regulatory elements has been challenging in the context of developing tissues where material is limited and cell types are mixed. To identify regulatory sites during sex determination, we subjected Sertoli cells from mouse fetal testes to DNaseI-seq and ChIP-seq for H3K27ac. DNaseI-seq identified putative regulatory sites around genes enriched in Sertoli and pregr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
44
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
4
1

Relationship

2
7

Authors

Journals

citations
Cited by 41 publications
(46 citation statements)
references
References 87 publications
2
44
0
Order By: Relevance
“…Wt1 gene was one of the genes upregulated in the absence of Foxl2 (Supplementary Material, Fig. S1C): in addition to a FOXL2 peak found near the Wt1 transcription starting site, another FOXL2bound region was found in the newly identified gonad-specific Wt1 enhancer region (20). A transgenic reporter model for this enhancer demonstrated that this regulatory region drives Wt1 expression in the Sertoli cells of the fetal testis.…”
Section: Identification Of Potential Target Genes Of Foxl2 In the Fetmentioning
confidence: 95%
“…Wt1 gene was one of the genes upregulated in the absence of Foxl2 (Supplementary Material, Fig. S1C): in addition to a FOXL2 peak found near the Wt1 transcription starting site, another FOXL2bound region was found in the newly identified gonad-specific Wt1 enhancer region (20). A transgenic reporter model for this enhancer demonstrated that this regulatory region drives Wt1 expression in the Sertoli cells of the fetal testis.…”
Section: Identification Of Potential Target Genes Of Foxl2 In the Fetmentioning
confidence: 95%
“…Studies examining the regulation of genes during mouse gonadal development have been conducted and are often considered a valid option for initial investigations in humans [Maatouk et al, 2017]. However, across the genome there is 41-89% difference between human and mouse transcription factor binding sites [Odom et al, 2007], and enhancer marks in multiple species have shown even less conservation at only 10-22% between different mammalian species [Schmidt et al, 2010].…”
Section: Structural Mapping Of the Genomementioning
confidence: 99%
“…Much attention in the field turned to addressing the question of how Sox9 is regulated. Twenty-five years later, this line of work culminated in the discovery of an enhancer element more than 500 kb upstream of Sox9 based on analysis of the chromatin landscape (Maatouk et al 2017, Garcia-Moreno et al 2019. Deletion/mutation of this enhancer leads to male-to-female sex reversal in mice and humans (Gonen et al 2018).…”
Section: Genetic Studies Identified Other Key Genes In the Sex Determmentioning
confidence: 99%
“…Interestingly, Lef1, which encodes a protein downstream of Wnt signaling, is a direct target of CBX2, as is another key gene in the ovary pathway, Foxl2 (Garcia-Moreno et al 2019). The identification of regulatory elements across the genome in XX and XY supporting cells using DHS and ATACseq methods (Maatouk et al 2017, Garcia-Moreno et al 2019, combined with histone data (Garcia-Moreno et al submitted) and ChIP-seq approaches for important transcription factors, may reveal how male or female fate is stabilized by repression of the alternative fate.…”
Section: Epigenetic Regulationmentioning
confidence: 99%